Indigenous and Scientific Knowledge in the Farming System: A Case of Urban Agriculture in Kageshwori-Manohara Municipality - Sapkota, Kanhaiya (Tribhuvan University Journal, 2018)
This study aims to analyse some contradictions and the interface between scientific and local knowledge on urban agriculture based on the one hundred and five households survey in Kangeshwori-Manohara low-lying Area. Semi-structure questionnaires interviews, key informant survey, field observations as well as categorization techniques were used for both qualitative and quantitative data and information. The farmers had changed their production from traditional to intensive, market-oriented agriculture. The transition had made tem to adopt wider range of improved farming techniques that means the by and large had entered into economically viable production, and also sustainable in terms of nutrient balance. The farmers’ practices had indicated some extent of link between scientific and indigenous knowledge.